Hydrological modelling as a tool for interdisciplinary workshops on future drought. (April 2018) - Rangecroft, S; Birkinshaw, S; Rohse, M; Day, R; McEwen, L; Makaya, E; Van Loon, AF
Transformative interdisciplinary methods and tools are required to address crucial water-related challenges facing societies in the current era of the Anthropocene. In a community-based study in the Limpopo basin of South Africa, physical and social science methods were brought together to run interdisciplinary workshops aimed at enhancing preparedness for possible future drought. To generate storylines for the workshops, relevant scenarios were modelled using a catchment-scale hydrological model, SHETRAN. Set up using freely available data, local knowledge, and narrative-based group interviews on past experiences of drought, the model acted as a locally-relevant tool for prompting discussions about potential future drought impacts, responses and preparedness, and to stimulate the production of community future narratives. In this paper, we discuss the elements involved in the modelling process: the building of the model through an interdisciplinary approach; setting up the model with limited data; and the translation of the model results into storylines for the workshops. We found that by using this methodology scientific grounding was given to the workshop storylines, and that the local context of the model and the engaging approach of creating narratives encouraged participant involvement in discussions about the future. The method of generating these future stories was an important process for the participants in developing their thinking about possible futures, preparedness and adaptation. In this paper we show how this alternative approach of using a hydrological model has benefits and we discuss the limitations and lessons of the approach for future interdisciplinary research.